EFFECT OF SUPPLEMENTAL RUMEN BYPASS LYSINE AND METHIONINE ON DIGESTIBILITY AND EFFICIENCY OF NUTRIENTS IN GROWING JAFFRABADI HEIFERS - Odedra, MD; Ravikala, R; Gajera, AP (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
An experiment was conducted to evaluate incorporation of rumen protected lysine (LYS) and methionine (MET) on nutrient efficiency, digestibility of nutrients and plane of nutrition in 18 Jaffrabadi buffalo heifers of an organized Farm. Animals (6 each) receiving either of the dietary treatments for 180 days, divided into 12 periods each of 15 days: T1- DCP requirement met through concentrate mixture alone, T2- DCP requirement met through cottonseed cake and concentrate mixture (50:50) and T3- DCP requirement met through concentrate mixture plus supplementation of rumen bypass LYS and MET @ 5.0 g and 2.5 g/day/animal, respectively. Intakes of CP, DCP and TDN were in linearly increasing order according to growth, but the intakes were not significantly (P>0.05) affected due to periods or treatments. The CP and DCP efficiency (kg/kg gain) was 1.68±0.23, 1.53±0.07, 1.50±0.07 and 1.27±0.17, 1.16±0.05, 1.17±0.06, respectively, for T1, T2 and T3 treatments. The corresponding values for TDN efficiency (kg/kg body weight gain) were 7.92± 1.01, 7.73±0.36 and 7.09±0.32 for T1, T2 and T3, respectively. The CP, DCP and TDN efficiency was neither affected significantly due to experimental rations nor with periods. Treatment effect on digestion coefficients of experimental rations for DM, EE, CF, CP, NFE and OM was non-significant (P>0.05). Though the DMI was at par, DCP, TDN intake and Nutrient intake per unit metabolic body weight were lower and so also DE, ME intakes compared to ICAR recommended levels. However, protein energy ratio was at par in all the experimental groups with ICAR levels.
Keywords: Jaffrabadi heifers; Nutrients intake; Bypass methionine and lysine; growth efficiency